Sex and the genuine marriage: consummation and conjugality in Canadian citizenship. Issue 5 (4th July 2019) - Challborn, Margot R.; Harder, Lois
ABSTRACT: The idea of consummation as definitive of a marriage seems antiquated today. Yet, consummation operates as a central criterion in determinations of a 'genuine marriage' in Canadian immigration law. Drawing on the marriage and migration literature, theorizations of sexual citizenship, and critical multiculturalism, we explore recent judicial considerations of consummation in Canadian family sponsorship adjudications. We searched the CanLII database (a Canadian database of legislation and judicial records) for the keywords 'non-consummation' and 'genuine marriage' and identified 68 cases. Of these cases, three primary themes emerged: the use of consummation as a 'technology of love' – a requirement for assessing the authenticity of the spousal relationship and hence the worthiness of sponsorship; the discursive construction of sexual and gendered norms in expectations around marital intimacy, and the articulation of liberal tolerance and the cultural other in the assessments of genuine marriages among primarily racialized Canadians or permanent residents and their foreign spouses. We challenge these discursive narratives and conclude by arguing that instead of consummation as the basis for genuine marriage, the Law Commission of Canada's 'close personal relationship' model is a better way to assess the 'genuineness' of relationships for determining Canadian citizenship.